A Bazaar Sustaining the Function for 400 Years: Spice Bazaar (Egyptian Bazaar) of Istanbul - Ozguven, Yekta; Durhan, Sila (CSAAR PRESS-CENTER STUDY ARCHITECTURE ARAB REGION, 2010)
The Spice Bazaar constructed in the 17th century, is the arasta of Yeni Mosque complex in Eminonu, in Historical Peninsula. It has surrounded by historical buildings such as a mosque, madrasah, tomb, commercial inns. The bazaar has always an extremely role in the urban history at all times. By accommodating the city as a spice market, always largely spices or similar herbal products have been sold in the bazaar. Thus, the bazaar has been always a shopping place that people prefer to go on purpose and also being belonged and committed to. Moreover, as a part of daily urban life, the bazaar is a welcoming point in Istanbul. Its large L block characterizes the Eminonu square in the view of Galata Bridge. But nowadays, the bazaar building is threatened by some adverse effects such as new additions closing its main facade, gift shops beginning to take herb and spice sellers' places and also underground roads that make it only a crossing point. Unfortunately these troubles cause the lack of relation with other historical heritages and the unhealthiness of the historical district. Only if, it would have better conditions on the purpose of use and been increased the environmental life qualities, Egyptian Bazaar could have enriched the urban life. On the other hand, the building's urban life quality can be increased by noticing the value of the building physically, socially, economically, culturally and architecturally. Therefore, it must be succeeded that bazaar's and also historical heritage's sustainability by saving its original function as a spice bazaar.
Keywords: Istanbul; bazaar; cultural and historical heritage; urban sustainability; functional sustainability; Architecture; Science & Technology - Other Topics; Urban Studies